Efficacy of mindfulness meditation in psychological distress exacerbated tinea cruris: A case report - Swathi Swaroopa Borra, Jemi Rachel Shaji, Ayilya Manomohan, Elsam Koshy, Sadagoban Gopal Krishnamoorthy (Journal of Applied Pharmaceutical Science, 2023)
Despite the possible behavioral and neurological benefits of mindfulness meditation (MM), its use in psychological distress exacerbated tinea cruris (TC) appears to be unexplored. This can be used with other interventions to reduce the distress associated with social anxiety and avoidance found in many skin conditions. MM practices shrink the amygdala, and in response, the prefrontal cortex becomes thicker which is associated with awareness, concentration, and decision-making. This case report examines the efficacy of MM in psychological distress exacerbated TC. A 33-year-old female patient with a history of recurrent TC was treated with antifungal medications at first and had no improvement due to observed psychological distress, but later with MM in conjunction with antifungals, her condition improved and complete resolution was seen after 8 weeks of treatment and no recurrence was observed with MM single-handedly without any antidepressant medication use. This case report indicates the improvement of the patient when meditation was added along with other interventions as the patient was in psychological distress, which was assessed by administering scales prior to and later to management.
Keywords: Jock itch, tinea c